AN INVESTIGATION INTO PROBLEMS OF INTERNET ACCESS AND USE IN DAR ES SALAAM, TANZANIA - Mutula, Stephen M.; Ahmadi, Mzee M.M. (Malaysian Journal of Library and Information Science, 2000)
The Internet wave has had a positive impact in many aspects of national life including the economic, social, educational, political and scientific sectors. The Tanzanian government has recognised the role of the Internet in national development and is making efforts to enhance Internet access and use in the country. The Government’s efforts in this regard include the enactment of a national science and technology policy, liberalizing the telecommunication sector, licensing several Internet service providers, setting up a regulatory body to oversee the privatisation of the telecommunications sector, reduction of import duty and other tariffs on software and hardware. Despite these efforts, there has been no significant increase in access and use of the Internet in Dar es Salaam and the whole of Tanzania. The study presents the results of a survey carried out on users to determine some of the problems limiting their Internet access and use in Dar es Salaam, Tanzania. The findings in usage are also presented. The results show that poor infrastructure, lack of awareness, unfriendly regulatory framework, high access charges are some of the factors limiting Internet access and use in Dar es Salaam, Tanzania.